Tactile Massage as Part of the Caring Act: A Qualitative Study in Short-Term Emergency Wards. (March 2016) - Airosa, Fanny; Falkenberg, Torkel; Öhlén, Gunnar; Arman, Maria
Aims and Objectives: The aim of this study was to illuminate the nursing staff's lived experiences and meaning in giving tactile massage (TM) while caring for patients in short-term emergency ward.Method: Data were collected through individual qualitative interviews with six nurses and eight assistant nurses working with TM in short-term emergency wards in two hospitals in Sweden. The narratives were analyzed using a phenomenological hermeneutical method.Findings: Nurses experienced providing TM to patients as a present awareness in connection with compassion for the patient. TM provided the nurses with a tool to ease patient suffering and pain. Three dimensions were found where touch became a tool of doing, was an aware presence as a mindful being, and was embodied in a human-to-human connection with a changed caregiver.Conclusion: Given the current high-tech health care system with overcrowded units and a shortage of nursing staff, TM could be included as a caring tool to improve the caring in caregiving, allowing nurses to act in aware presence by touch to encourage health and well-being for both the patient and themselves.